Atypical information-use in children with autism spectrum disorder during judgments of child and adult face identity. Issue 4 (19th May 2018) - Ewing, Louise; Pellicano, Elizabeth; King, Harriet; Lennuyeux-Comnene, Laura; Farran, Emily K; Karmiloff-Smith, Annette; Smith, Marie L
ABSTRACT: Unusual patterns of fixation behavior in individuals with autism spectrum disorder during face tasks hint at atypical processing strategies that could contribute to diminished face expertise in this group. Here, we use the Bubbles reverse correlation technique to directly examine face-processing strategies during identity judgments in children with and without autism, and typical adults. Results support a qualitative atypicality in autistic face processing. We identify clear differences not only in the specific features relied upon for face judgments, but also more generally in the extent to which they demonstrate a flexible and adaptive profile of information use.